Mechanical reduction of frictional resistance of ninety-degree PVC conduit elbows for installation of large conductors - Disberger, Jay (Kansas State University, 2018)
This paper presents the results of an experiment that was purposed with introducing the physical feasibility of a conceptual product that would mechanically reduce frictional resistance of schedule 40 PVC conduit elbows during the installation of large conductors. In the current construction industry, there is a well established and code driven convention for the construction of PVC conduit. For the installation of building service conductors, significant energy is required to pull conductors through the conduit. The service feed is the most expensive and restrictive pull on most projects strictly due the weight of the large conductors which are heavily resistant to deformation. The forces involved necessitate stringent requirements on maximum pull lengths and maximum degrees bent between pull boxes. Cost and risk of costly installation damage are also major characteristics of service feed pulls. The resistance to pulling and highest concentrations of internal forces throughout any conductor pull is located at the elbows or bends. This study is a scaled experimental-based initial establishment of expected evidence to support the feasibility of a product that would essentially reduce the required force to pull large conductors. This product is idealized as a factory PVC elbow that contains mechanical rollers along the inside face of the elbow where the conductors theoretically make the most contact during pulling. This product will ultimately be more expensive, but would be expected to benefit the project by reducing installation time, possibly reduce the number of pull boxes required, and reduce the risk of damaging conductors or conduits. The experiments described in this paper reflect a small-scale set that establishes trends of varying any one significant parameter for single conductor pulls through a single ninety-degree factory PVC elbow. While further research into multi-conductor feeders must be conducted in order to establish full justification for the product development was expected at the onset, the results of this study show that even further additional research must be conducted to resolve an ambiguity on which a definitive conclusion depends. Due to unforeseen or predicted parameters impacting the reduction of frictional resistance throughout the experimentation, the results both support and counter any benefit of applying mechanical means to reduce frictional resistance. The percentages of reduction range from -37% to +24% across the study’s results. The hypothesized sources of the ambiguity that counter expectations can only be verified by future studies. However, the evidence from this study can become definitively directional for the pursuit or lack there of for further investigating the benefits of the idealized product.
Keywords: Conductor pulling; Frictional resistance; Building electrical systems; Electrical power; Scaled modeling; Conduit elbows